Association of Elevated Amyloid Levels With Cognition and Biomarkers in Cognitively Normal People From the Community - Petersen, Ronald C. (JAMA Neurol, 2016)
IMPORTANCE: The role of amyloid in the progression of Alzheimer disease (AD) pathophysiology is of central interest to the design of randomized clinical trials. The presence of amyloid has become a prerequisite for enrollment in several secondary prevention trials for AD, yet the precise effect of elevated amyloid levels on subsequent clinical and biomarker events is less certain. OBJECTIVE: To explore the effect of elevated amyloid levels on subsequent changes in cognition and biomarkers. DESIGN, SETTING, AND PARTICIPANTS: A total of 564 cognitively normal individuals (median age, 78 years) from the Mayo Clinic Study of Aging, a population-based longitudinal study in Olmsted County, Minnesota, with serial cognitive data were selected for this study. The data used in this study were collected from January 12, 2006, to January 9, 2014. Individuals included in this study had undergone magnetic resonance imaging, fluorodeoxyglucose positron emission tomography (FDG-PET), and Pittsburgh Compound B (PiB) PET at baseline were not cognitively impaired at baseline and had at least 1 clinical follow-up. A subset of 286 individuals also underwent serial imaging. Elevated amyloid level was defined as a standardized uptake value ratio of greater than 1.5 on PiB PET. Associations with baseline amyloid status and baseline and longitudinal change in clinical and imaging measures were evaluated after adjusting for age and hippocampal volume. APOE4 effects were also evaluated. MAIN OUTCOMES AND MEASURES: Cognitive measures of memory, language, attention/executive function, visuospatial skills, PiB levels, hippocampal and ventricular volumes, and FDG-PET measures. RESULTS: At baseline, 179 (31.7%) individuals with elevated amyloid levels had poorer cognition in all domains measured, reduced hippocampal volume, and greater FDG-PET hypometabolism. Elevated amyloid levels at baseline were associated with a greater rate of cognitive decline in all domains (0.04 to 0.09 z score units per year) except language and a greater rate of amyloid accumulation (1.6% per year), hippocampal atrophy (30 mm(3) per year), and ventricular enlargement (565 mm(3) per year). Elevated amyloid levels were also associated with an increased risk of mild cognitive impairment (hazard ratio, 2.9; 95% CI, 1.7–5.0, and hazard ratio, 1.6; 95% CI, 0.9–2.8, for PiB+ APOE4 carriers and PiB+ noncarriers, respectively, compared with PiB− noncarriers). These associations were largely independent of APOE4. CONCLUSIONS AND RELEVANCE: In persons selected from a population-based study, elevated amyloid levels at baseline were associated with worse cognition and imaging biomarkers at baseline and with greater clinical decline and neurodegeneration. These results have implications for the design of randomized clinical trials for AD.